Pedunculated subserosal leiomyoma with torsion, a rare cause of abdominal pain: A case report. Issue 5 (3rd February 2023) - Chang, Ching-Tang; Lee, Sieh-Yang; Chang, Ching-Di
Abstract : Introduction: Acute abdominal pain caused by torsion of the pedunculated subserosal leiomyoma is rare. Miss diagnosis can lead to ischemia, necrosis, and subsequent peritonitis which may cause significant morbidity. Torsion of the leiomyoma should be recognized as a surgical emergency and once suspected, early surgical intervention should be considered. Patient concerns: A 28-year-old woman with a medical history of uterine leiomyoma presented to our emergency department because of acute onset right lower abdominal pain. Diagnoses: The computed tomography was performed which demonstrated multiple leiomyomas of variable sizes and a subserosal leiomyoma located at right lower abdomen with poor contrast enhancement. Interventions: The gynecologist was consulted, and myomectomy was performed. The intraoperative finding showed a pedunculated subserosal leiomyoma with torsion. Outcomes: She underwent myomectomy for the twisted pedunculated subserosal leiomyoma as well as other leiomyomas and was discharged with a favorable outcome. Conclusions: Torsion of the leiomyoma is a surgical emergency as delayed in treatment may lead to marked morbidity. Once suspected, the gynecologist must be consulted, and surgical intervention should be considered.